Comparison of spatial filters and features for the detection and classification of movement-related cortical potentials in healthy individuals and stroke patients. (27th July 2015) - Jochumsen, Mads; Niazi, Imran Khan; Mrachacz-Kersting, Natalie; Jiang, Ning; Farina, Dario; Dremstrup, Kim
Abstract: Objective. The possibility of detecting movement-related cortical potentials (MRCPs) at the single trial level has been explored for closing the motor control loop with brain–computer interfaces (BCIs) for neurorehabilitation. A distinct feature of MRCPs is that the movement kinetic information is encoded in the brain potential prior to the onset of the movement, which makes it possible to timely drive external devices to provide sensory feedback according to the efferent activity from the brain. The aim of this study was to compare methods for the detection (different spatial filters) and classification (features extracted from various domains) of MRCPs from continuous electroencephalography recordings from executed and imagined movements from healthy subjects ( n  = 24) and attempted movements from stroke patients ( n  = 6) to optimize the performance of MRCP-based BCIs for neurorehabilitation. Approach. The MRCPs from four cue-based tasks were detected with a template matching approach and a set of spatial filters, and classified with a linear support vector machine using the combination of temporal, spectral, time-scale, or entropy-based features. Main results. The best spatial filter (large Laplacian spatial filter (LLSF)) resulted in a true positive rate of 82 ± 9%, 78 ± 12% and 72 ± 9% (with detections occurring ∼200 ms before the onset of the movement) for executed, imagined and attempted movements (stroke patients). The best feature combination (temporal and spectral) led to pairwise classification of 73 ± 9%, 64 ± 10% and 80 ± 12%. When the detection was combined with classification, 60 ± 10%, 49 ± 10% and 58 ± 10% of the movements were both correctly detected and classified for executed, imagined and attempted movements. A similar performance for detection and classification was obtained with optimized spatial filtering. Significance. A simple setup with an LLSF is useful for detecting cued movements while the combination of features from the time and frequency domain can optimize the decoding of kinetic information from MRCPs; this may be used in neuromodulatory BCIs.